Variations in domestic energy efficiency by property, neighbourhood and local authority type: where are the largest challenges for the net-zero transition of the UK’s residential stock? - Buyuklieva, Boyana; Oléron-Evans, Thomas; Bailey, Nick; Dennett, Adam (Frontiers in Sustainability, 2024)
Achieving net zero in the UK requires radical improvements in energy efficiency in housing combined with the decarbonisation of domestic heating. Achieving the energy efficiency goals requires a systems approach which takes account of variations at the level of individual properties but also the levels of neighbourhood and the local governance context. Our study provides insights into the scale of the challenge and how this varies by spatial context using property-level energy efficiency measures from Energy Performance Certificates data between 2008-22 and covering approximately half of the residential stock in England and Wales. We use a series of multi-level models to provide insights into how differences in energy efficiency are related to factors at each scale. Our findings show that, while the great majority of variation lies at the property level, there is some variation at the neighbourhood (Output Area -OA) level. Controlling for property characteristics, energy efficiency is slightly higher in neighbourhoods characterised by more disadvantaged populations. There is little evidence, therefore, that more affluent groups are either choosing to move into more energy-efficient housing or making a significant effort to invest in energy efficiency. While government support has been targeted at more disadvantaged groups, this suggests that more will need to be done to motivate or require more widespread action if the UK is to meet its net zero targets. There is only small variation at the local authority (LA) level suggesting little difference in the range or effectiveness of strategies by that tier of governance, but also that all households face similar challenges going forwards.